THE CHANGE OF POLITICAL ROLES AND POWER OF ADIREKSARN FAMILY - kanthai, duangkamol (King Prajadhipok’s Institute Journal, 2020)
The study of “The Change of Political Roles and Power of the Adireksarn Family” has two objectives. Firstly, one aim was to study the way the Adireksarn family won votes and maintained its political power. Secondly, an aim was to study the growth and political, economic, and social changes, as well as changes in the private sector, in Saraburi Province. This study uses qualitative research method drawing on documentary sources of information and also primary data gathered througho in-depth interviews with people in the Adireksarn family. The Adireksarn family plays an important political role in Saraburi. The study revealed how the Adireksarn family built and maintains its political base in Saraburi. Furthermore, the study suggested that economic growth, economic, social, and political change, and creation of new private business groups in Saraburi has resulted in the diminishing of the Adireksarn family’s political role and power and the state of the family’s political base.